Effect of Supplementary Food Substitution of Sea Urchin Gonads (Diadema Setosum) on TSH Hormone, Height, and Weight of Stunted Toddlers in Soropia District - Hariani, Hariani; Fahturrahman, Teguh; Astuti, Trina; Wiralis, Wiralis (Postgraduate, University of Mataram, 2023)
Stunting results in generational loss due to decreased ability to work productivity and IQ. Thyroid Stimulating Hormone (TSH) plays an important role in the growth process, in chronic growth hormone deficiency conditions will spur the incidence of stunting. The purpose of the study was to determine the effect of supplementary food formula substitution of sea urchin gonads (Diadema Setosum) on Thyroid hormone, height and weight of stunted toddlers in Soropia District. This experiment using RCT (Randomized Control Trial) design. The sample in this study were stunted toddlers in Soropia District.Â Â The formula uses a substitution of sea urchin gonads (Diadema Setosum) which is given in one portion of additional food.Â Additional food in the form of nuggets, sausages, bakwan. The formula is given for 3 months with a frequency of every day for 90 days. The Results to be achieved that the availability of supplementary food formulations substituting sea urchin gonads, nutritional content of supplementary food formulas, energy and protein consumption data, data on body height and thyroid hormone levels, body height and weight before and after supplementary food formulas